The crossover novel contemporary children's fiction and its adult readership / Rachel Falconer. - Falconer, Rachel (Children's Literature and Culture,, 2008)
While crossover books such as Rowling?s Harry Potter series have enjoyed enormous sales and media attention, critical analysis of crossover fiction has not kept pace with the growing popularity of this new category of writing and reading. Falconer remedies this lack with close readings of eight works of crossover fiction.